Antihyperglycemic potential of Gentianella gilgiana (Reimers) Fabris ex J.S. Pringle for in vitro intestinal glucose absorption in diabetic albino rats - Guevara-Vásquez, Ana María del Carmen (2019)
Objective: To evaluate the antihyperglycemic potential of the Gentianella gilgiana (Reimers) Fabris ex J.S. Pringle infusion for in vitro intestinal glucose absorption in Rattus norvegicus of the Holtzman strain with chemically-induced diabetes. Materials and methods: The study had an experimental and analytical design. A phytochemical screening of the whole plant was carried out. For the in vitro study, twenty male albino rats were induced with diabetes using alloxan monohydrate (Sigma-Aldrich, Saint Louis, MO, USA) at a dose of 120 mg/kg bw administered by intraperitoneal route, and then randomly distributed into two groups of ten albino rats each. After ten days, they were sacrificed to extract an intestinal segment using the everted intestinal sac technique, and measure the glucose transport and absorption. In the control group (everted intestines incubated in Krebs-Henseleit solution containing glucose) and the experimental group (intestines incubated in Krebs-Henseleit solution containing glucose plus the Gentianella gilgiana (Reimers) Fabris ex J.S. Pringle infusion at 10% w/v), basal samples of fluids were taken from incubation, and then other samples were taken at 15, 30, 45 and 60 minutes to quantify the glucose from the mucous and serous compartments using the glucose oxidase enzymatic method. Results: Lower concentrations of absorbed glucose were observed in the intestinal serous compartment of the experimental group (G. gilgiana) with a statistically significant difference compared to the control group (p <0.05). Conclusions: The Gentianella gilgiana (Reimers) Fabris ex J.S. Pringle infusion exhibits a significant antihyperglycemic potential by decreasing the in vitro intestinal glucose absorption in diabetic albino rats.